Isolation of components of the chloroplast protein import machinery - Schnell, Danny; Kessler, Félix; Blobel, Gunter (My University, 1994)
Components of the protein import machinery of the chloroplast were isolated by a procedure in which the import machinery was engaged in vitro with a tagged import substrate under conditions that yielded largely chloroplast envelope-bound import intermediates. Subsequent detergent solubilization of envelope membranes showed that six envelope polypeptides copurified specifically and, apparently, stoichiometrically with the import intermediates. Four of these polypeptides are components of the outer membrane import machinery and are associated with early import intermediates. Two of these polypeptides have been characterized. One is a homolog of the heat shock protein hsp70; the other one is a channel-protein candidate.
Keywords: SIGNAL RECOGNITION PARTICLE; ENVELOPE CONTACT SITES; TRANSIT PEPTIDE; PHOSPHATE TRANSLOCATOR; PRECURSOR PROTEINS; MEMBRANES; RECEPTOR; BINDING; IDENTIFICATION; SEQUENCE